90K, an interferon-stimulated gene product, reduces the infectivity of HIV-1 - Lodermeyer, Veronika; Suhr, Kristina; Schrott, Nicola; Kolbe, Christian; Stürzel, Christina M.; Krnavek, Daniela; Münch, Jan; Dietz, Christian; Waldmann, Tanja; Kirchhoff, Frank; Goffinet, Christine (My University, 2013)
Background:
In response to viral infections, interferons induce the transcription of several hundred genes in mammalian cells. Specific antiviral functions, however, have only been attributed to a few of them. 90K/LGALS3BP has been reported to be an interferon-stimulated gene that is upregulated in individuals with cancer or HIV-1 infection.
Results:
Here, we show that 90K expression dose-dependently decreased the particle infectivity of HIV-1 progeny. The lower infectivity of released particles correlated with reduced virion incorporation of mature envelope glycoproteins gp120 and gp41. Further, proteolytic processing of the gp160 precursor and surface expression of gp120 in the producer cell were impaired in the presence of 90K expression. In contrast, expression of Gag, Nef and Vpu, and virus release were not grossly affected by 90K expression. 90K-imposed restriction occurred in the absence of direct interaction of 90K with HIV-1 Env or entrapment of Env in the ER. The cell-associated, but not the secreted species of 90K, mediated the antiviral effect. A truncated version of human 90K, solely consisting of the two intermediate domains, displayed a similar antiviral activity as the full-length wildtype 90K, indicating that the N-terminal SRCR-like domain and the C-terminal domain are dispensable for 90K’s antiviral activity. The murine homolog of 90K, CypCAP (Cyclophilin C-associated protein), neither modulated particle infectivity of HIV-1 nor lowered the virion incorporation of mature gp120, suggesting a species-specific mode of action. 90K was expressed at basal levels in TZM-bl cells and in primary macrophages, and at low levels in CD4+ T-cells and PBMCs. 90K’s susceptibility to IFN-mediated stimulation of expression was cell type-specific. siRNA-mediated knockdown of 90K in TZM-bl cells and primary macrophages enhanced the incorporation of Env glycoproteins into progeny virions, boosted the particle infectivity of released HIV-1, and accelerated HIV-1 spread. Conversely, treatment of HIV-1 infected macrophages with IFN-α induced 90K expression and lowered the particle infectivity of HIV-1.
Conclusions:
Thus, 90K constitutes a novel antiviral factor that reduces the particle infectivity of HIV-1, involving interference with the maturation and incorporation of HIV-1 Env molecules into virions.
Keywords: 004